2011
DOI: 10.3390/rs3112403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Spectral Indices for Assessing Fire Severity in Chaparral Ecosystems (Southern California) Using MODIS/ASTER (MASTER) Airborne Simulator Data

Abstract: Abstract:Wildland fires are a yearly recurring phenomenon in many terrestrial ecosystems. Accurate fire severity estimates are of paramount importance for modeling fire-induced trace gas emissions and rehabilitating post-fire landscapes. We used high spatial and high spectral resolution MODIS/ASTER (MASTER) airborne simulator data acquired over four 2007 southern California burns to evaluate the effectiveness of 19 different spectral indices, including the widely used Normalized Burn Ratio (NBR), for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 73 publications
(161 reference statements)
6
55
1
Order By: Relevance
“…Other studies obtained similar results, e.g., better discrimination capabilities of BAI [18,22,28], Greenness [24,62], or MIRBI in shrub-savannah ecosystems [25,27,52]. Although NBR is often considered the best SI for burned area mapping short time after fire and therefore widely used for burn severity assessments [7,19,21,23,[27][28][29], our results demonstrated that in certain vegetation types other SI would offer a better option. The limitations of NBR for immediate post-fire assessment were already pointed out by Roy et al [76].…”
Section: Summary Of Results Which Si Should We Choose?supporting
confidence: 79%
See 1 more Smart Citation
“…Other studies obtained similar results, e.g., better discrimination capabilities of BAI [18,22,28], Greenness [24,62], or MIRBI in shrub-savannah ecosystems [25,27,52]. Although NBR is often considered the best SI for burned area mapping short time after fire and therefore widely used for burn severity assessments [7,19,21,23,[27][28][29], our results demonstrated that in certain vegetation types other SI would offer a better option. The limitations of NBR for immediate post-fire assessment were already pointed out by Roy et al [76].…”
Section: Summary Of Results Which Si Should We Choose?supporting
confidence: 79%
“…Initially designed for burned area extraction, NBR is the most popular spectral index used for burn severity assessments with different sensors in several ecosystems around the world. In numerous comparative analyses, NBR proved to be one of the most efficient SI [14,19,21,23,28]. In time series analyses, NBR showed good correlations with field-based composite burn index scores several years after a fire, thus representing an efficient tool for vegetation recovery monitoring [29,30].…”
Section: Index Full Name Abbreviation Equation Referencementioning
confidence: 94%
“…Spectral vegetation indices have been proven useful in monitoring seasonal variations in vegetation development (phenological cycle) [43,44], as well as post-fire plant regeneration [45,46]: strong correlations were observed between the NDVI and various biophysical vegetation parameters, such as Leaf Area Index (LAI), the fraction of photosynthetically active radiation (fPAR) or vegetation abundance [47]. Although relationships between burn severity, NDVI and LST values seem quite clear, few studies have explored these [8,48,49]. There are indications that the inclusion of thermal information in spectral indices for severity mapping improves their performance [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal infrared (TIR) remote sensing provides spatially distributed estimates of land-surface temperature (LST) that can be used for detecting wild fires [1,2], mapping land surface energy fluxes and evapotranspiration [3][4][5][6][7][8][9][10], monitoring urban heat fluxes [11][12][13][14][15] and detecting drought [7,8,16]. For many of these applications, TIR data are required at relatively fine resolution.…”
Section: Introductionmentioning
confidence: 99%